Estimation of egg weight from some external and internal quality characteristics in quail by using various data mining algorithms - ÇELIK, SENOL; SENGÜL, TURGAY; INCI, HAKAN; SÖÐGÜT, BÜNYAMIN; SENGÜL, A YUSUF; KUZU, ÇIGDEM; AYASAN, TUGAY (The Indian Journal of Animal Sciences, 2018)
The objective of this study was to compare the predictive performance of some data mining algorithmsimplemented in the estimation of egg weight (EW), some egg quality traits measurements in quail. These qualitytraits are albumen weight (AW), yolk weight (YW), specific weight (SW), albumen index (AI), albumen height(AH), yolk index (YI), shell weight (SHW), shell thickness (SHT), Haugh unit (HU) and shape index (SI). Forcomparing the predictive performance of these algorithms in Model, goodness of fit criteria such as coefficient ofdetermination (R2%), adjusted coefficient of determination (Adj. R2%), coefficient of variation (CV%), SD ratio,root mean square error (RMSE), relative approximation error (RAE), and Pearson correlation coefficient, betweenobserved and predicted values were calculated. The heaviest average EW of 13.516 g was obtained from thesubgroup of those having AW > 8 cm. The results showed that the analysis based on exhaustive CHAID might beuseful for further researches linked with characterization of quail egg better than those provided by CART andCHAID algorithms.